Flooding in Nepal: Analyzing Incidents, Human Casualties, and Property Losses - Danai, Anisha; Adhikari, Pitri Bhakta (Perspectives on Higher Education, 2024)
A flood occurs when river water overflows due to intense monsoon rainfall, presenting a significant disaster in the low-lying areas of Nepal. This research provides insights into various aspects of floods, including the total number of incidents, fatalities, affected households, and estimated losses that occurred over the past thirteen years. Nepal is divided into three main geographical regions: Mountains, Hills, and Terai. Rainwater from the Mountains and Hills flows into the Terai region, significantly increasing the risk of flood disasters there. In this study, data accessed through website of Government of Nepal (GON), Nepal Disaster Risk Reduction (DRR) Portal, selecting Ministry of Home Affairs (MoHA), source is used for the collection of data since 2011 A.D. Statistical tools are used on the analysis of the collected data and plotting the graph. The peak occurrence of flood incidents coincides with the monsoon season, particularly in July, August, and September. This study aims to analyze flood patterns, incident occurrences, fatalities, and property losses in recent years. It is found through the study that a minimum of one person dies after almost two flood incidents, as well as almost 35 families is directly affecting by a single flood incident in recent decade. Besides that, flood causes an estimated loss of about millions to billions each year in Nepal and the death pattern over months shows gaussian like distribution.